10 Pre-operative multimodality imaging for LVAD. (9th April 2018) - Yingchoncharoen, Teerapat
Abstract : Cardiac imaging, particularly echocardiography, plays a critical role in patient selection and in predicting post-operative complications. There are several pre-implantation imaging red flags that guide intraoperative concomitant procedures consideration and may predict post-operative outcomes. The pre-operative imaging should include assessment of the left ventricle (LV), especially with attention to the LV cavity size, the presence of prominent trabecular or LV thrombus which may lead to LV assist device (LVAD) suction events, inflow cannula obstruction or thromboembolic events. Assessment of right ventricular (RV) function is one of the most important pre-operative evaluation. This talk will discuss the advantages and disadvantages of imaging modality in pre-operative assessment of RV function for LVAD patients, and the assessment of valvular function. The presence of aortic insufficiency, mitral stenosis or tricuspid insufficiency that is greater than moderate degree must be corrected. The presence of patent foramen ovale may lead to post-operative persistent hypoxaemia. Aortic aneurysm, aortic dissection and aortic atheroma may impact cannula placement, leading to dissection progression or increased risk of thromboembolic stroke. These findings are red flags and should be documented and discussed with the surgeon before the time of surgery. Reference: . Kassi M, Estep JD. Role of multimodality imaging in patients with left ventricular assist device. Curr Opin Cardiol2016;31(5):510–22.